Formative Assessment in Sundanese Language Learning for Middle School Students in West Java - Kuswari, Usep; Ruhaliah, Ruhaliah; Nugraha, Haris Santosa; Darajat, Danan (International Journal of Language and Culture, 2024)
The background of this research is the untouched assessment model of student-friendly learning of the Sundanese language. Therefore, Student Friendly Assessment is very important because 1) increases learning motivation: When students feel understood and acknowledged for their diverse potential, their learning motivation increases. 2) Student-friendly assessments can help create a positive and inclusive learning environment, will also help create a safe learning environment because student-friendly assessments help create a safe learning environment, where students feel comfortable participating, sharing opinions, and asking questions without fear judged. 3) Improving Teaching Effectiveness: Through student-friendly assessments, teachers can identify students' strengths and weaknesses more comprehensively. Thus, teachers can adapt teaching methods to suit individual needs. 4) Flexibility in Implementation, it is important to provide a variety of ways for students to demonstrate their understanding. It is carried out by taking into account a variety of written and unwritten formative assessments, such as unwritten assessments in the form of class discussions, plays, project products, presentations, and oral tests, while written tests include reflections, journals, essays, posters, and written tests. The purpose of this research is to describe the latticework of student-friendly assessment models of learning Sundanese learning assessment models in learning Sundanese, as well as guidelines for formative assessment models in student-friendly learning of the Sundanese language that can provide information for schools, both in terms of content, coverage, format and time of delivery as well as optimal benefits for learning Sundanese language and literature at junior high school level in West Java. The method used in this research is a development model using the Research and Development research genre which aims to produce a product in the form of a student-friendly assessment model of learning Sundanese and an assessment guide for learning Sundanese language and literature at junior high school levels in West Java. The expected results of this study are the adjusted student-friendly Sundanese learning assessment grids based on the Sundanese language learning assessment model in junior high school, student-friendly assessment models in Sundanese language learning that have been developed and tested, as well as guidelines for formative assessment models in learning Sundanese at junior high school level in Jawa Barat.